Evaluation and optimization of DNA for RAPD analysis of Terminalia tomentosa - Wani, Mohd Rafi; Rathore, Rajesh; Malik, Javid Ahmad (International Journal of Scientific Research in Biological Sciences, 2019)
Forest tree species are more demanding than other plants to extract a pure and high quality of DNA for molecular genetics. A modified protocol for Terminalia tomentosa genomic DNA extraction was developed by introducing modification on Cetyl Trimethyl Ammonium Bromide (CTAB) method. The principle modification we involved in the present study are; PVP (Polyvinylpyrrolidone), column based purification step and copper acetate solution. Fresh leaves were collected from the tender shoots of mature trees of Terminalia tomentosa. The yield and the purity of genomic DNA was monitored by measuring optical density (O.D.) at A260 and A280 with a Nanodrop Spectrophotometer (ND2000).The highest amount of genomic DNA with the best quality was isolated from column based step in the CTAB extraction buffer. The yield of DNA by this modified method was approximately 100-153 µg per 200mg of fresh leaf tissue. Both ratios were 2.1 and 1.8 respectively, indicating the absence of contaminating metabolites. The obtained DNA was then tested for suitability by random amplification of polymorphic DNA (RAPD)-PCR analysis. Clear band pattern were observed for DNA isolated from four accessions of Terminalia tomentosa, collected from different geographical locations of Achanakmar Amarkantak Biosphere Reserve, Central India. The results clearly indicate the utility of DNA for genetic diversity analysis of this forest tree species.